2016
DOI: 10.1002/tox.22308
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of EGF receptor signaling and NLRP12 inflammasome in fine particulate matter‐induced lung inflammation in mice

Abstract: Epidemiological studies have shown that exposure to ambient fine particulate matter (PM ) is associated with respiratory diseases. Lung inflammation is a central feature of many pulmonary diseases, which can be induced by PM exposure. However, the mechanisms underlying PM -induced lung inflammation remain unclear. To characterize the role of epidermal growth factor receptor (EGFR) and inflammasome in PM -induced lung inflammation in mice, 30 BALB/c mice were intrabroncheally instilled with saline and PM suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…AGPS and Tudor-SN serve a key role in the adjustment of tumor angiogenesis, and are expressed highly in multiple tumor tissue types and are associated with the prognosis of patients (16). In the present study, it was determined that AGPS silencing or suppression inhibited the proliferation and migration of glioma U87MG cells, validating the biological function of AGPS in glioma (17).…”
Section: Discussionsupporting
confidence: 59%
“…AGPS and Tudor-SN serve a key role in the adjustment of tumor angiogenesis, and are expressed highly in multiple tumor tissue types and are associated with the prognosis of patients (16). In the present study, it was determined that AGPS silencing or suppression inhibited the proliferation and migration of glioma U87MG cells, validating the biological function of AGPS in glioma (17).…”
Section: Discussionsupporting
confidence: 59%
“…The PM 2.5 suspension was stored at 4°C for use. The composition of PM 2.5 was determined using inductively coupled plasma‐mass spectrometry and gas chromatography‐mass spectrometry, which had been reported by our previous study …”
Section: Methodsmentioning
confidence: 92%
“…As to cardiovascular system, NLRP3 inflammasome has been given its possible involvement in PM 2.5 ‐induced heart injury in our previous research . In the previous study, we found the upregulation of NLRP3 protein using IHC and IL‐18 mRNA that may be regulated by NF‐KB signal pathway with RT‐PCR in PM 2.5 ‐induced cardiac tissues . And, the expression of NLRP3 protein may be prepared for inflammasome activation, but it is not the marker of NLRP3 inflammasome activation .…”
Section: Introductionmentioning
confidence: 89%
“…As known to all, the particles aggregate easily in sterile saline. For this reason, the PM 2.5 suspension was sonicated to make particles dispersed just before intratracheal instillation into mice (Farina et al, 2011;Jin et al, 2017). We also determined that the chemical composition of PM 2.5 samples was rich in some metals such as Zn, Al, Pb, Fe and part of PAHs.…”
Section: Discussionmentioning
confidence: 99%